2004
DOI: 10.1073/pnas.0308054101
|View full text |Cite
|
Sign up to set email alerts
|

Selective expression of IL-7 receptor on memory T cells identifies early CD40L-dependent generation of distinct CD8 + memory T cell subsets

Abstract: Several recent studies have demonstrated that T-helper cell-dependent events during the initial priming period are required for the generation of CD8 ؉ T cell-mediated protective immunity. The underlying mechanisms of this phenomenon have not yet been determined, mostly because of difficulties in studying memory T cells or their precursor populations at early stages during immune responses. We identified IL-7 receptor (CD127) surface expression as a marker for long-living memory T cells, most importantly allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
439
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 428 publications
(467 citation statements)
references
References 33 publications
26
439
2
Order By: Relevance
“…In the model by Sallusto et al [11], CCR7 + CD62L + antigen-experienced CD8 T cells circulate through secondary lymphoid tissue and are termed central memory cells, while CCR7 -CD62L +/-effector memory CD8 T cells migrate to peripheral sites. However, the process of T cell differentiation in response to antigen is highly complex, and other cell surface receptors such as CD7, CD27, CD28, CD45RA, CCR5 and CD127 can be used to identify functionally distinct subsets of effector and memory T cells [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the model by Sallusto et al [11], CCR7 + CD62L + antigen-experienced CD8 T cells circulate through secondary lymphoid tissue and are termed central memory cells, while CCR7 -CD62L +/-effector memory CD8 T cells migrate to peripheral sites. However, the process of T cell differentiation in response to antigen is highly complex, and other cell surface receptors such as CD7, CD27, CD28, CD45RA, CCR5 and CD127 can be used to identify functionally distinct subsets of effector and memory T cells [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these cells expressed CCR5, a chemokine receptor which enables homing to the inflammatory chemokines RANTES, MIP-1a and MIP1b [29]. A small proportion of the tonsil CXCR5 + CD8 T cells expressed the IL-7 receptor CD127, which, as data from murine models indicate, may be important for long-term memory T cell generation [15,16]. A majority of CXCR5 + CD8 T cells were CD57 -, but a clear subset with intermediate to high expression representing about a third of cells was also observed (Fig.…”
mentioning
confidence: 99%
“…These are (i) a proliferation phase that involves the growth and differentiation of naïve CD8 + T cells into effector T cells; (ii) a contraction or transition phase that entails the transition from the large population of effector CD8 + T cells to a smaller population (≈ 5-10%) of long-lived CD8 + memory T (Tm) cells (2); and (iii) a maintenance phase that is comprised of long-term CD8 + Tm cell survival in the host. The long-lived CD8 + Tm cell population can be rapidly reactivated and expanded upon Ag restimulation for recall responses.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies using LCMV-infected mice have shown that these two molecules can mark CD8 + memory cell precursors [26][27][28]31], other studies using peptide-pulsed DCs or peptide immunization have shown that IL-7R is not a marker for such precursors [38][39][40][41]. Antigen-presenting cells expressing thymic leukemia antigen TL can boost CD8αα expression by T cells, and CD8αα expression induces IL-7Rα expression [29].…”
Section: Discussionmentioning
confidence: 99%
“…3B). Since IL-7R and CD8αα have been reported to be early markers of memory CD8 + T cells [26][27][28][29][30][31], IL-7R and CD8aa expression were tracked using flow cytometry on CD8 + T cells after the initial inoculation. No increases in CD8 + IL-7R + or CD8αα + cells were detected in blood or spleen in any of the mice we tested over the first 14 days after the second initial vaccination (data not shown).…”
Section: Vaccination With Socs1-downregulated Bmdcs Enhanced Ova-specmentioning
confidence: 99%